Unleashing Employee Engagement: Exploring the Influence of Human Resource Practices in a Local Municipality in South Africa - Isabirye, Dr. AK; Moloi, Prof. KC (Journal of Ecohumanism, 2025)
This research investigates the potential of human resource policies to increase employee engagement in a South African local government municipality. The research employed qualitative naturalistic interpretive methods with semi-structured interviews as data collections tools. Data was collected from ten participants code-named P1 to P10. The study was guided by three core questions: i). What are the current HR practices within the studied Municipality, and how do employees perceive them? To what extent do these HR practices influence employee engagement levels? iii). What recommendations can be made to enhance HR practices to improve employee engagement? Findings revealed among others that recruitment and selection, training and development, performance management systems, and employee recognition influenced employee engagement in the municipality. The research suggests that the municipality should support professional development alongside transparent hiring practices and fair performance management as well as reasonable employee appreciation. It also recommends establishing positive workplace culture together with work-life balance programmes to increase employee engagement. Additionally, it was recommended that municipal managers should establish HR strategies which support all employees and fulfill their needs to build a positive workplace environment. By incorporating these elements into their HR strategy, the municipality can enhance employee engagement, leading to better performance and service delivery. This research demonstrates how HR strategies in local governments enable organisations to enhance employee morale and workplace engagement.